1999
DOI: 10.1677/joe.0.1620011
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian steroids regulate 24p3 expression in mouse uterus during the natural estrous cycle and the preimplantation period

Abstract: We examined 24p3 expression in the mouse uterus at various stages of the natural estrous cycle and during the preimplantation period. The level of 24p3 mRNA appeared intensively in proestrus and estrus, then declined sharply from metestrus to diestrus. Consistent with this observation, 24p3 protein was abundant in proestrus, decreased from estrus to metestrus and declined to a very low level in diestrus. The uterine 24p3 expression closely overlapped with the estradiol (E 2 ) surge in proestrus and estrus but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 26 publications
4
46
2
Order By: Relevance
“…The observation that induction of NGAL correlates with apoptosis led to the hypothesis that NGAL is a pro-apoptotic factor (Huang et al, 1999;Ryon et al, 2002). This hypothesis was furthered strengthened by the observation that NGAL induced the apoptosis of neutrophils through an autocrine pathway (Devireddy et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…The observation that induction of NGAL correlates with apoptosis led to the hypothesis that NGAL is a pro-apoptotic factor (Huang et al, 1999;Ryon et al, 2002). This hypothesis was furthered strengthened by the observation that NGAL induced the apoptosis of neutrophils through an autocrine pathway (Devireddy et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…NGAL was reported to participate in various functions, including apoptosis and innate immunity, but primarily in the response to bacterial infection [19,20]. NGAL is also expressed in multiple tissues such as kidney, liver, uterus, and bone marrow [21][22][23]. Several reports have suggested that NGAL is a sensitive biomarker for various forms of kidney injuries [24][25][26].…”
Section: Anthropometric Parameters Blood Pressure and Blood Collectionmentioning
confidence: 99%
“…We previously showed that LCN2 mediates autocrine signaling within the endometrial epithelium (Huang et al 1999, Lee et al 2012. As LCN2 is a stress protein (Lin et al 2007), we used a 1% FBS culture medium, which causes nutrient-deprivation stress, to induce LCN2 production.…”
Section: Emt Of Primary Endometrial Epithelial Cells Cultured In Nutrmentioning
confidence: 99%